GAMBARAN KEMATANGAN KARIER SISWA KELAS X SMA SWASTA JAKARTA - Arianne .; Margaretha Purwanti (MANASA, 2019)
A descriptive study aimed in describing the career maturity of the 10th-grade students at one private high school in Jakarta. The study participants were 49 people consisting of 29 male students and 20 female students. The age range of participants is 15-16 years old. Participants in this study still have difficulty planning their studies and future careers. These conditions indicate students have not reached career maturity by the stage of career development. Having a career maturity is one of the essential for students with regards to planning their further study and future career. This study used the Modified Indonesian version of the Career Maturity Inventory (hereinafter referred to as CMI) and group interviews. The CMI measured the dimensions of consistency, realistic career choice, competence in making careers decision, and attitudes on making a career decision. Based on the quantitative data processing shows that 28.9% of 10thgrade students have a high level of maturity. However, from group interviews, the students shared that they still had doubts about their abilities and did not yet explore more about the university major they chose. The study concludes that most respondents who have maturity but are still less skilled in planning and making career decisions. The results of the study can be used as a reference for developing counselling guidance programs for 10th-grade students.